Induction of Barangan Banana shoot (Musa acuminata L.) from North Nias through Tissue Culture by giving 2,4-D and Kinetin - Destarius Zebua; Suci Rahayu; Saleha Hanum (Universitas Negeri Medan, 2015)
The research on induction of banana barangan shoot (Musa acuminata L.) from North Nias through tissue culture by giving 2,4-D and kinetin was conducted in the Laboratory of Tissue Culture University of North Sumatera from May until October 2014. The main objective of this research was to know the explants of banana weevil in apical and basal position with growth regulator 2,4-D with kinetin which are able to induce shoots from callus initials. On this research, the treatment tested for induction of shoots was growth regulators 2,4-D in the concentration 0 mg/L, 1 mg/L, 1,5 mg/L, 2 mg/L and 2,5 mg/L with growth regulators kinetin in the concentration 0 mg/L, 5 mg/L, 6 mg/L, 7 mg/L and 8 mg/L. The research was designed using Completely Randomized Design (CRD) two factorial with repetition of experiment. The results of research showed that the interaction between concentration of 2,5 mg/L 2,4-D with 5 mg/L kinetin was fastest (79 days) forming the shoot derived from explant basal part. The concentration of 2,5 mg/L 2,4-D with 5 mg/L kinetin produced the average number of shoots formed for 3.00 and average number of highest shoots for 1.50 cm. Keywords: Musa acuminata, weevil, initiation, callus, shoot, induction, barangan banana, 2,4-D, kinetin.